Shifting occupation dynamics in the Madriu-Perafita-Claror valleys (Andorra) from the early Neolithic to the Chalcolithic: the onset of high mountain cultural landscapes - Orengo, Hector A.; Palet Martínez, Josep M.; Ejarque, Ana; Miras, Yannick; Riera-Mora, Santiago (Elsevier, 2014)
The Madriu–Perafita–Claror valleys (MPCV) (Eastern Pyrenees, Andorra) were the focus of a multidisciplinary microregional landscape research project that aimed to study the long term shaping of this UNESCO World Heritage Site in the category of cultural landscape. The study area is situated on a glacial modelled high mountain environment ranging from 1250 to 2800 m.a.s.l.